ECOLOGICAL BALANCE AND RESOURCE SUSTAINABILITY: A VISION OF ECONOMIC SCARCITY IN THE TECHNOLOGICAL AGE - Ali Omran Hussein; Haidar Eidan Kareem (Scholar Express Journals, 2025)
This research represents a review article to study the relationship between environmental balance and resource sustainability as a vision of economic scarcity in the technological era. Advanced technology effectively contributes to increasing the efficiency of resource use, as German and Chinese solutions achieved 25% success in increasing the efficiency of economic growth based on innovations in renewable energy technology. The results confirmed that advanced technology contributes significantly to environmental sustainability and economic wealth, such as artificial intelligence, data analysis, and renewable energy management. For example, Japan and South Korea achieved a 15% reduction in emissions. Advanced technology has many benefits, but it can face significant challenges, such as high costs and increasing e-waste problems.
Keywords: Environmental balance; economic scarcity; natural resources